Effects of Marichromatium gracile YL28 on the nitrogen management in the aquaculture pond water. (November 2019) - Zhu, Bitong; Chen, Shicheng; Zhao, Chungui; Zhong, Weihua; Zeng, Runying; Yang, Suping
Graphical abstract: Highlights: Denitrification and assimilatory nitrate reduction contributed to N management. Excessive nitrogen loss was averted during the N removal processes. In-situ eliminated NO2 − and NH4 + without adding external carbon sources. YL28 showed the great potential to be used as the safe probiotics. Abstract: Nitrogen pollution in aquaculture needs the efficient and cost-effective in-situ technology. This study aims to apply Marichromatium gracile YL28 to in-situ bioremediation and test its ability to maintain the nitrogen balance in aquaculture. In laboratory aquaculture system, approximately 99.96% of nitrite (1 mg/L) was removed within 7 d through denitrification coupled with assimilatory nitrate reduction. Ammonium (3.5 mg/L) of 95.6% was directly assimilated by YL28 within 7 d. Moreover, in zero exchange water from shrimp ( Penaeus vannamei ) aquaculture field trials (20 days), YL28 significantly reduced the ammonium accumulation (0.6 mg/L) and 99.3% of nitrite (1.25 mg/L). Toxicological studies with the Institute of Cancer Research (ICR) mice and Oryzias melastigma indicated that M. gracile YL28 can be safely applied in aquatic ecosystems. All results demonstrate that strain YL28 has high promise for future applications of removing inorganic nitrogen and maintaining the nitrogen balance from in-situ aquaculture.